Fabrication of highly electrically conductive polypropylene/polyolefin elastomer/multiwalled carbon nanotubes composites via constructing ordered conductive network assisted by die‐drawing process. Issue 39 (27th July 2022) - Zhao, Zhongguo; Zhou, Shengtai; Ai, Taotao; Li, Yapeng; Yang, Qi; Jia, Shikui; Tang, Dahang
Abstract: In this work, a facile strategy is proposed to prepare highly electrically conductive polypropylene (PP)/polyolefin elastomer (POE)/multiwalled carbon nanotubes (MWCNTs) composites with ordered conductive networks using a house‐made die‐drawing apparatus. Results showed that increasing either die‐drawing speed or drawing ratio led to an increase of crystallinity by 10% and orientation factor by 0.15 for PP, respectively, which played an important role in tuning the electrical conductivity and mechanical properties. Prior to die‐drawing process, MWCNTs were selectively distributed in POE domains, resulting in a remarkable increase of electrical conductivity. The prevailing high‐stress field during die‐drawing process was able to deform MWCNTs‐enriched POE domains to ordered microfibrillar structure, as confirmed by morphology observations. This resulted in a further increase of electrical conductivity for die‐drawn PP/POE/MWCNTs composites when compared with that of MWCNTs‐containing counterparts without die‐drawing. Moreover, both the tensile strength and elongation at break for die‐drawn PPCNTE30 composites were increased by 20% and 127% as compared with their counterparts without die‐drawing treatment. Abstract :